Acquired protein C deficiency in a child with acute myelogenous leukemia, splenic, renal, and intestinal infarction - Farhat, Hussein (2011)
We report the case of a 6-year-old boy diagnosed with acute promyelocytic leukemia (AML-M3V) when he presented with pallor, abdominal pain, anorexia, and fatigue. Induction chemotherapy was started according to the AML-BFM 98 protocol along with Vesanoid (ATRA, All-trans retinoic acid). On the sixth day of induction, he developed splenic and gallbladder infarcts. Splenectomy and cholecystectomy were performed while chemotherapy induction continued as scheduled. Four days later, he developed ischemic areas in the kidneys and ischemic colitis in the sigmoid colon. Hypercoagulation studies showed severe deficiency of protein C. Tests showed protein C 16% (reference range 70–140%), protein S 87% (reference range 70–140%), antithrombin III 122% (reference range 80–120%), prothrombin time 13.6 s (reference = 11.3), INR (international normalized ratio) 1.21, partial thromboplastin time 33 s (reference = 33), fibrinogen 214 mg/dl, D-dimer 970 μg/ml, factor II 98%, and that antinuclear antibody, antiphospholipid antibodies, mutation for factor II gene (G20210A), and mutation for Arg506 Gln of factor V were all negative (factor V Leiden). There was no evidence of clinical disseminated intravascular coagulation (DIC). He was treated with low molecular weight heparin and did well. He continues to be in complete remission 7 years later with normal protein C levels. Acquired protein C deficiency can occur in a variety of settings and has been reported in acute myelocytic leukemia. However, clinically significant thrombosis in the absence of clinical DIC, such as our case, remains extremely rare.